Perlindungan Hukum Satwa Terhadap Eksploitasi Berkaitan Dengan Ekosistem - Gede Dius Waisnawa Cahyadi; I Nyoman Gede Sugiartha; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2025)
Exploitation means exploitation on a large scale, usually in plantations, mining, or exploitation for personal gain. The existence of exploitation requires massive conservation efforts by all affected groups, because all components of nature need each other and play an equally important role in maintaining the balance of ecosystem resources. This includes law enforcement on the existence of protected wildlife. The problems are: 1) What are the legal protections for protected sea turtles? 2) What legal responsibilities do the perpetrators face when exploiting protected sea turtles? Research and understand the legal protection of protected sea turtles and the legal consequences for perpetrators of exploitation of protected sea turtles. Liability for perpetrators of protected turtle exploitation may include criminal intimidation under Article 21(2)(a) jo. Article 40(2) of the Law on Biological Protection provides a maximum imprisonment of 5 years and a fine of one hundred million Rupiah.